O211 First SEEG examination in University of Pécs. Issue 9 (September 2017) - Toth, Marton; Horvath, Zsolt; Doczi, Tamas; Kuperczko, Diana; Janszky, Jozsef
Abstract : We present the first stereotactic EEG (SEEG) case implanted at the Department of Neurology, University of Pécs. The patient had a pharmacoresistent focal epilepsy with solely nocturnal seizures. The epilepsy disease started in 2009 (at 19 years of age). The lack of febrile seizures and hippocampal atrophy, and the frequent secondarily generalizations lead us against mesiotemporal origin. Results of noninvasive video-EEG monitor (left frontotemporal onset), brain MRI (suspicion of right temporal dysgenesis), FDG-PET (hypometabolism in left temporal lobe, left ventral insula, left orbitofrontal cortex) were discordant, therefore, the patient was implanted by deep electrodes for localizing the seizure onset zone (SOZ). Five electrodes were implanted into left frontal lobe and another five electrodes into the left temporal lobe, and finally, one electrode into the right collateral sulcus. Despite the (beginner's) difficulties, our intervention was conclusive -  SOZ was defined to the left temporal pole and lateral temporal cortex, thus the resective option became available. (The presentation will contain video-recorded seizures with SEEG-recordings.)